2021
DOI: 10.18488/journal.61.2021.93.497.506
|View full text |Cite
|
Sign up to set email alerts
|

Professional Development Activities and Teacher Performance

Abstract: Learning to teach reflectively is a lifelong process that is strengthened through the active engagement of varied professional development activities inside or outside the school. This study assessed the quality of instruction and professional development activities in a well-known university in Cebu, the Philippines, where it determined teachers' teaching competencies and perception in their professional development activities, issues, and concerns. It utilized a quantitative-descriptive research design where… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…Garcia (2021) suggested that to maximize the activation of 21st-century skills, teachers should modify their instruction to follow 21st-century approaches. Similarly, Padillo (2021) underlined that participation in diverse professional development activities facilitates the transmission of best practices among teachers from other institutions. Table 2 displays the teaching effectiveness of mathematics teachers as perceived by the students.…”
Section:  Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Garcia (2021) suggested that to maximize the activation of 21st-century skills, teachers should modify their instruction to follow 21st-century approaches. Similarly, Padillo (2021) underlined that participation in diverse professional development activities facilitates the transmission of best practices among teachers from other institutions. Table 2 displays the teaching effectiveness of mathematics teachers as perceived by the students.…”
Section:  Results and Discussionmentioning
confidence: 99%
“…It is argued to be the key to learning state-of-the-art teaching strategies and practices that can help enhance teachers' performance related to their expertise and impact student learning (Hammond et al, 2017). Padillo et al (2021) stated that the caliber of teachers determines the quality of instruction. The opportunity to improve classroom instruction and meet students' and parents' learning expectations in school may be contingent on whether professional development initiatives and programs are structured to address current needs.…”
Section:  Introductionmentioning
confidence: 99%
“…Compared to the number of countries in the world which number in the hundreds, the publication of teacher performance in 20 years averages 19 articles per year. Even though this theme is central because teacher performance is related to the level of quality of education in a country (Junio-Sabio & Manalo, 2020;Padillo et al, 2021;Tambunan et al, 2021), teacher performance requires serious attention. Sharing information about teacher performance from various sides will make it easier to improve teacher performance (Kaswi et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Although they have distinct characteristics, these organizations come together with a common dedication to enhancing educational methods and student results. By providing teacher educators with resources, strategies, and support, they all contribute to teachers' ongoing professional development (Padillo et al, 2021). This improves their ability to meet the needs of all students and prepares them for success in an educational environment that is always changing (Ulmane-Ozolina et al, 2019).…”
Section: Sponsors Of the Webinarsmentioning
confidence: 99%
“…Active involvement in ongoing professional development is crucial for teacher-educators who aim to enhance their teaching abilities in the current dynamic educational setting (Padillo et al, 2021). Participating in webinars is one way to do it in their busy schedule (Tanucan & Uytico, 2021).…”
Section: Introductionmentioning
confidence: 99%